2014
DOI: 10.1111/jpy.12251
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparison of toxin‐producing isolates of Dinophysis acuminata from New England and Canada

Abstract: Following the identification of the first toxic isolate of Dinophysis acuminata from the northwestern Atlantic, we conducted detailed investigations into the morphology, phylogeny, physiology, and toxigenicity of three isolates from three sites within the northeastern U.S./Canada region: Eel Pond and Martha’s Vineyard, Massachusetts, and the Bay of Fundy. Another isolate, collected from the Gulf of Mexico, was grown under the same light, temperature, and prey conditions for comparison. Despite observed phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 56 publications
4
15
0
2
Order By: Relevance
“…The ability to use the metrics outlined by Tong et al. () to speciate these Dinophysis was consistent with statistically significant differences in morphometric characteristics. Univariate ANOVA on morphometric data, with post hoc REGWF multiple comparisons tests, indicated that species within the Dinophysis acuminata ‐complex could be separated from each other using a series of morphometrics (Fig.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…The ability to use the metrics outlined by Tong et al. () to speciate these Dinophysis was consistent with statistically significant differences in morphometric characteristics. Univariate ANOVA on morphometric data, with post hoc REGWF multiple comparisons tests, indicated that species within the Dinophysis acuminata ‐complex could be separated from each other using a series of morphometrics (Fig.…”
Section: Resultssupporting
confidence: 64%
“…In all, 322 individually picked Dinophysis cells were examined using the six metrics outlined in Tong et al. (). From all samples analyzed, five primary morphospecies were identified, measured, and photographed from 24 preserved water samples, a clonal culture of D. acuminata (DADE01) established from Torquay Canal, Delaware, and a clonal culture of D. ovum (DoSS 3195) established from Freeport, Texas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Het toxine gehalte en de toxine samenstelling van verschillende fytoplanktonstammen kan sterk verschillen. Zo is het bijvoorbeeld van sommige cyanobacteriën en de dinoflaggelaat D. acuminata bekend dat bepaalde stammen niet in staat zijn toxines te produceren, terwijl andere stammen van dezelfde soort dat wel kunnen [87,[116][117][118][119].…”
Section: Gebruikte Datasetsunclassified
“…• Het toxine gehalte in de cel binnen een stam kan verschillen als gevolg van veranderende groeiomstandigheden en groeisnelheden [87,[116][117][118].…”
Section: Gebruikte Datasetsunclassified